2019
DOI: 10.1093/mnras/stz3207
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the planet–metallicity correlation for hot Jupiters

Abstract: We investigate the giant planet-metallicity correlation for a homogeneous, unbiased set of 217 hot Jupiters taken from nearly 15 years of wide-field ground-based surveys. We compare the host star metallicity to that of field stars using the Besançon Galaxy model, allowing for a metallicity measurement offset between the two sets. We find that hot Jupiters preferentially orbit metal rich stars. However, we find the correlation consistent, though marginally weaker, for hot Jupiters (β = 0.71 +0.56 −0.34 ) than i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 54 publications
(87 reference statements)
2
9
0
Order By: Relevance
“…HD 83443 is a solar mass K0 star, with more than twice the metallicity of the Sun. This enhanced metallicity is consistent the well-established giant-planetmetallicity correlation (e.g., Jones et al 2016;Ghezzi et al 2018;Osborn & Bayliss 2020;Fulton et al 2021). For the orbit fitting and derivation of planetary parameters, we adopt a stellar mass of 1.00 ± 0.03 M e (Delgado Mena et al 2019).…”
Section: Stellar Properties Of Hd83443supporting
confidence: 74%
“…HD 83443 is a solar mass K0 star, with more than twice the metallicity of the Sun. This enhanced metallicity is consistent the well-established giant-planetmetallicity correlation (e.g., Jones et al 2016;Ghezzi et al 2018;Osborn & Bayliss 2020;Fulton et al 2021). For the orbit fitting and derivation of planetary parameters, we adopt a stellar mass of 1.00 ± 0.03 M e (Delgado Mena et al 2019).…”
Section: Stellar Properties Of Hd83443supporting
confidence: 74%
“…Over twenty years ago, studies showed that stars hosting hot-Jupiters (giant planets in very short period orbits) are typically iron-enriched compared to the Sun (Gonzalez 1997;Santos, Israelian & Mayor 2001;Fischer & Valenti 2005). This trend has, however, weakened in more recent studies (Osborn & Bayliss 2019;Teske et al 2019). Similarly, the relationship between a star's iron abundance and the number of planets it hosts remains the subject of significant debate (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While high metallicities are expected for stars which host close-in giant exoplanets (Fischer & Valenti 2005), we find that WASP-47 and 55-Cancri have high metallicities even compared to the metallicity distribution for hot-Jupiter host stars. Osborn & Bayliss (2020) investigated this planet-metallicity correlation using a homogeneous sample of 217 hot Jupiter host stars. We find that WASP-47 is more metal rich than 96% of that sample, and 55-Cancri is more metal rich than 94%.…”
Section: Discussionmentioning
confidence: 99%